Multimetallic lanthanide complexes: Using kinetic control to define complex multimetallic arrays - Sørensen, T; Faulkner, S (American Chemical Society, 2018)
Kinetically inert lanthanide complexes are proving to be highly effective building blocks for the preparation of complex heterometallic architectures, allowing complete control of metal ion domains, which cannot be achieved under thermodynamic control. Kinetic stability may render perceivable labile coordination bonds more durable than several types of covalent interactions. For complexes in clinical use, the significance of kinetic stability cannot be overstated, and this Account treats the topic accordingly. Kinetically inert complexes can be used as building blocks for elaborate synthesis. For instance, it is now possible to prepare heterometallic lanthanide complexes containing two or more different lanthanide ions by linking kinetically robust complexes together. This approach can yield bimetallic (f–f′ or d–f) and trimetallic (f–f′–f″) lanthanide complexes. In this Account, we describe our studies exploiting the slow dissociation of lanthanide complexes derived from 1,4,7,10-tetraazadodecane-1,4,7,10-tetraacetic acid (DOTA) related ligands to link complexes together through synthetic manipulation of pendent groups on the ligand skeleton or through coordination of bridging donor groups to a d-block metal center. In the course of this work, we have developed a variety of such methods, ranging from peptide coupling and diazotization to Ugi and click chemistry and have also explored the use of alternative strategies that combine orthogonal protecting group chemistry with sequential complexation of different lanthanide ions or that use self-assembly to deliver well-defined multimetallic systems. These well-defined bimetallic systems also have considerable scope for exploitation. Since the earliest studies, it has been clear that there is potential for application in the burgeoning field of molecular imaging. Heterometallic lanthanide complexes can be used as single-molecule bimodal imaging agents through incorporation of MRI active and luminescent components. Alternatively, conventional luminescence methods can be exploited in conjunction with lanthanide luminescence. In the simplest cases, a single lanthanide can be used to achieve a switchable response in combination with a transition metal complex. Bimetallic f–f′ complexes allow the full potential of the approach to be realized in systems in which one lanthanide responds to changes in the concentration of an analyte, while a second lanthanide center can be used to define the concentration of the probe itself. This offers a new solution to the old dichotomy of ratiometric imaging that can potentially be applied widely.